Histologic Features Suggestive of Shallow Placental Implantation: Maternal–Placental Relevance and Site-Specific Implications - Ravikumar, Gayatri; Kamath, Padmavathi S.; Shekharappa, Chandrakala Bada (American Journal of Perinatology, 2025)
Shallow placental implantation (SPI) contributes to adverse pregnancy outcomes. Identification of histopathological features of SPI and its clinical associations with site-specific implications remains under-explored, which forms the basis for this study.This retrospective study included 182 singleton placentas over 25 weeks of gestation submitted for histopathological examination. Features of SPI was identified based on extravillous trophoblast (EVT) persistence in the decidua, parenchyma, or membranes/chorionic disc. Associations of features of SPI (any SPI, multiple SPI when more than one SPI lesion was present, and site-specific features of SPI) with clinical and placental outcomes were analyzed.At least one feature of SPI was present in 58.8% placentas, with multiple features in 26.9%. The most common site was membranes/chorionic disc (40%). Features of SPI was present in parenchyma in 24.2% and in decidua in 20.3%. Presence of SPI features was significantly associated with preeclampsia (p = 0.0001), fetal growth restriction (FGR; p = 0.012), Cesarean delivery (p = 0.007), and chronic hypertension (p = 0.014) and negatively with PROM (p = 0.0009). Placental findings with significant association were lower placental weight (p = 0.042), infarction (p = 0.015), significant fibrin (p = 0.005), maternal (p < 0.001) and fetal (p = 0.014) vascular malperfusion. The birth weight was significantly lower when SPI features were present (p = 0.013), though no significant difference was observed in major neonatal morbidities. Basal plate myometrial fibers showed association with multiple SPI (p = 0.023).Site-specific analysis revealed SPI features in parenchyma to be significantly associated with oligohydramnios and increased neonatal morbidities (hematological, gastrointestinal, and overall), in addition to other adverse outcomes associated with SPI. Decidual features of SPI were additionally associated with maternal diabetes, but showed limited neonatal impact beyond low birth weight.SPI features correlate significantly with major obstetric conditions, birth weight, and placental vascular pathology. Site-specific analysis shows parenchymal SPI has the greatest clinical impact, particularly on neonatal morbidities. Recognition and site-specific documentation enhance its value as an additional parameter within the maternal vascular malperfusion (MVM) spectrum.
Keywords: shallow placental implantation; placenta; extravillous trophoblast; maternal vascular malperfusion; preeclampsia